A retrospective study on the diagnostic values of magnetic resonance examination of the anal canal in the classification of anal fistula - Yongli Wu; Min Wang (Journal of the Pakistan Medical Association, 2025)
Objective: To explore the diagnostic value of magnetic resonance imaging of the anal canal in classifying anal fistula. Method: The retrospective study was conducted at Yongli Wu, Danyang Hospital of Traditional Chinese Medicine, Danyang, Jiangsu, China, and comprised clinical data of patients with anal fistula treated from April 2021 to March 2022. All the patients had undergone magnetic resonance imaging scanning and surgical treatment, with surgical resection specimens sent to pathology. Pathological results served as the gold standard for the diagnosis. The consistency between preoperative magnetic resonance imaging and surgical results in diagnosing anal fistula classification was analysed. Data was analysed using SPSS 21. Results: Of the 79 patients, 58(73.4%) were males and 21(26.6%) were females. The overall mean age was 43.12±12.12 years, and mean disease duration was 7.11±1.76 months. Surgery found 75(94.9%) low, 4(5.1%) high, 42(53.2%) simple, 37(46.8%) difficult, 1(1.3%) internal, and 78(98.7%) external anal fistulae. Preoperative magnetic resonance imaging showed 74(93.7%) low, 5(6.3%) high, 43(54.4%) simple, 35(44.3%) difficult, 1(1.3%) internal and 78(98.7%) external anal fistulae. Surgery and magnetic resonance imaging detected anal fistulas similarly (p>0.05). Surgery found 36(45.6%) inter-sphincteric, 26(32.9%) trans-sphincteric, 11(13.9%) supra-sphincteric and 6(7.6%) extra-sphincteric anal fistulae. Pre-operative magnetic resonance imaging indicated 34(43%) inter-sphincteric anal fistulas, 25(31.6%) trans-sphincteric, 11(13.9%) supra-sphincteric and 6(7.6%) extra-sphincteric. Further, surgery detected 87(110.1%) internal orifices, 25(31.6%) abscesses, 79(100%) major fistulas, 67(84.8%) external orifices, and 22(27.8%) branch pipes. The corresponding values for magnetic resonance imaging were 84(106.3%), 25(31.6%), 76(96.2%), 66(83.5%) and 20(25.3%) respectively (p>0.05). Conclusion:Magnetic resonance imaging of the anal canal was found to have a high accuracy in diagnosing and classifying anal fistula. Keywords: Anal fistula, Magnetic resonance, Surgical pathology, Diagnostic value.